Analisis Penerapan Akuntansi Lingkungan terhadap Biaya Operasional Pengolahan Limbah - Hasanah, Nurmala; Sujaya, Fista Apriani; Puspitasari, Meliana (Universitas Gorontalo, 2025)
Environmental accounting refers to the recording of environmental costs as part of an organization’s responsibility toward its surrounding environment, particularly regarding the management of waste or by-products generated by the organization. This study aims to examine the environmental management activities undertaken to reduce the operational impact on the environment and to evaluate the environmental accounting reporting implemented by a hospital. The research was conducted at Amira General Hospital, Purwakarta City, using a descriptive qualitative method. The results indicate that the hospital has effectively managed its waste, as evidenced by a dedicated report on environmental costs. Furthermore, the study found no internal or external failures in the hospital’s environmental management practices.